2001
DOI: 10.1159/000056265
|View full text |Cite
|
Sign up to set email alerts
|

Stress Markers in Relation to Job Strain in Human Service Organizations

Abstract: Background: Workers in human service organizations are often confronted with conflicting demands in providing care or education. The aim of this cross-sectional study was to relate levels of endocrine stress markers to perceived job strain in two human service organizations. Methods: Employees in two local units of the social insurance organization and two local units of the individual and family care sections of the social welfare in Sweden were selected and 103 employees participated (56% participation rate)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…It might be suggested that such stressors were not so important to health as the ones that were accompanied by hormone alterations [27, 28, 29]. …”
Section: Discussionmentioning
confidence: 99%
“…It might be suggested that such stressors were not so important to health as the ones that were accompanied by hormone alterations [27, 28, 29]. …”
Section: Discussionmentioning
confidence: 99%
“…The C-IBS and A-IBS patients are characterised by their psychological symptoms of anxiety and depression. Emotional strain is correlated to increased levels of prolactin and this could be one of the reasons for the prolactin increase in the C-IBS group [44] . Also in agreement with our results, Elsenbruch et al [12] found in a study on postprandial autonomic and cortisol responses that D-IBS patients elicited an enhanced sympathetic drive as measured by heart rate variability compared to the C-IBS patients and controls.…”
Section: Peer Reviewmentioning
confidence: 98%
“…Two studies (24,25) indicated that the cortisol concentration was greater in a high job-strain group, while four studies showed an insignificant association during work (13,22,26), mental tasks in a laboratory (27), or day off (13,22). Two other studies even showed lower cortisol concentrations among participants with high job strain (28) or with high job demands (29).…”
mentioning
confidence: 98%